PENGARUH UPAH BURUH KELAPA SAWIT TERHADAP TINGKAT KESEJAHTERAAN MASYARAKAT DESA SUNGAI ANTU - Susanti, Priska; Aminuyati, Aminuyati; Asriati, Nuraini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to determine the effect of the income of oil palm worker wages on the level of community welfare in Sungai Antu Village, Puring Kencana District, Kapuas Hulu Regency. The method used in this research is descriptive method. In this study a sample of 35 workers or laborers. The sampling technique in this research using  rondom sampling technique. Data collection uses indirect communication technique (questionnaire), and documentation study. The instrument test in this research is the validity test and the reability test. Data processing techniques in this research used simple regression  test with the help of the SPSS program. The results showed that the palm oil worker’s wage to the level of community welfare  Y = 6,485 + 0.835X. Based on the results of calculations using the SPSS program, t arithmetic of 14,434 while t table, so the degree of freedom df = nk or 35-2 = 33, then t table is 2,034 of these results compared between t arithmetic with t table that is (14,434> 2,034) and with a coefficient of determination (R2) 0.835 or 83,5% which means there is an influence between the ability to palm oil worker’s wage to the level of community welfare in Sungai Antu Village, Puring Kencana District, Kapuas Hulu Regency.Keywords: Labor Wages, Income, Publik Welfare